The Effectiveness of ICARE Model on Micro Teaching Subjects through Hybrid Learning Class - Yudi Hari Rayanto; Supriyo (CV. AFDIFAL MAJU BERKAH, 2022)
This research was started with a simple research question to find out the effectiveness of ICARE model implemented on teaching Micro Teaching subject whereas it was embedded in online and offline as a lesson plan in Hybrid learning class. In this research, the researcher used a descriptive qualitative research. It meant the researcher joined both the online class and an offline class to observe the real learning activity and for gaining the learners’ score for measuring the effectiveness of ICARE on Micro Teaching subject in a hybrid learning class. The researcher used two instruments they were observation field note and evaluation sheets. Field note observation was held to observe the learning activities in online in 10 while 4 meetings in offline were held through conducting test. Researcher prepared 20 items indicators which were used to obtain the learners’ score based on performance teaching test. The researcher used likert scale for determining the point gained by learners. The result from observation in online learning showed that mostly learners really enjoyed and were enthusiastic in joining online learning activity in 10 meetings. Meanwhile through the test in offline learning in 4 meetings, there were 7 Learners got more that 90 (excellence) and 8 learners got under 90 (satisfied). So, it was concluded that ICARE model was effective to be implemented altogether in teaching and learning activity in hybrid learning (online and offline) for gaining effective teaching and learning and fabulous fruitful.